Implementation of the Rights of Correctional Inmates According to Law Number 22 of 2022 Concerning Corrections - Harry Julius Pratama Manalu; Herlina Manullang; Jusnizar Sinaga (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research analyzes the implementation of the rights of correctional inmates based on Law Number 22 of 2022 concerning Corrections, which emphasizes a humanist approach in the correctional system. This law emphasizes that inmates still have basic rights, such as education, health, family visits, and mental and social training. Using normative-empirical research methods, this research examines the implementation of these regulations at the Medan Class I Penitentiary. The research results show that although these rights have been regulated in statutory regulations, their implementation still faces various obstacles, such as the limited number of correctional officers, overcapacity conditions, and a lack of facilities and health personnel. These obstacles hinder the optimization of the community system in achieving the goal of social reintegration for inmates. Therefore, strategic steps are needed from related parties to increase the effectiveness of providing the rights of inmates in order to achieve more optimal community goals.